Pengaruh Penerapan Standar Akuntansi Keuangan Entitas Mikro, Kecil dan Menengah (SAK EMKM) Terhadap penyusunan Laporan Keuangan - Sucianty, Faradilla Indah; Pardistya, Irfan Yoga (Peneliti.net, 2023)
The purpose of this study was to find out, analyse and describe the effect of applying SAK EMKM (Standard Financial Accounting for Micro, Small and Medium Entities) on the preparation of financial reports. The population in this study are MSME business actors who are registered with the Small and Medium Enterprises Cooperative Service in the culinary field in the district. Karawang. The total sample used was 50 MSME entrepreneurs in the district. Karawang. Data analysis using Descriptive Statistical Analysis, Reliability Test, Classical Assumption Test required such as Normality Test, Heteroscedasticity Test and Simple Linear Regression Analysis and Hypothesis Testing. The results showed that the application of SAK EMKM (Standards for Financial Accounting for Micro, Small and Medium Entities) has a significant effect on the preparation of financial reports.